Cadmium exposure is associated with increased transcript abundance of multiple heavy metal associated transporter genes in roots of hemp (Cannabis sativa L.) - Marabesi, Amanda O.; Nambeesan, Savithri U.; van Iersel, Marc W.; Lessl, Jason T.; Coolong, Timothy W. (Frontiers in Plant Science, 2023)
Industrial hemp (Cannabis sativa L.) has demonstrated promise for phytoremediation due to an extensive root system, large biomass, and ability to survive under relatively high levels of heavy metals. However, little research has been conducted to determine the impact of heavy metal uptake in hemp grown for medicinal use. This study evaluated the potential for cadmium (Cd) uptake and its impact on growth, physiological responses, and transcript expression of metal transporter genes in a hemp variety grown for flower production. The cultivar ‘Purple Tiger’ was exposed to 0, 2.5, 10, and 25 mg·L-1 Cd in a greenhouse hydroponic study in two independent experiments. Plants exposed to 25 mg·L-1 Cd displayed stunted plant growth characteristics, reduced photochemical efficiency, and premature senescence suggesting Cd toxicity. At the two lower concentrations of Cd (2.5 and 10 mg·L-1 Cd), plant height, biomass, and photochemical efficiency were not affected, with chlorophyll content index (CCI) being slightly lower at 10 mg·L-1 Cd, compared to 2.5 mg·L-1 Cd. There were no consistent differences between the two experiments in total cannabidiol (CDB) and tetrahydrocannabinol (THC) concentrations in flower tissues at 2.5 and 10 mg·L-1 Cd, compared to the control treatment. Root tissue accumulated the highest amount of Cd compared to other tissues for all the Cd treatments, suggesting preferential root sequestration of this heavy metal in hemp. Transcript abundance analysis of heavy metal-associated (HMA) transporter genes suggested that all seven members of this gene family are expressed in hemp, albeit with higher expression in the roots than in the leaves. In roots, CsHMA3 was up-regulated at 45 and 68 d after treatment (DAT), and CsHMA1, CsHMA4, and CsHMA5 were upregulated only under long term Cd stress at 68 DAT, at 10 mg·L-1 Cd. Results suggest that expression of multiple HMA transporter genes in the root tissue may be upregulated in hemp exposed to 10 mg·L-1 Cd in a nutrient solution. These transporters could be involved in Cd uptake in the roots via regulating its transport and sequestration, and xylem loading for long distance transport of Cd to shoot, leaf, and flower tissues.